Controvérsias na Anticoagulação Oral: Continuar ou Interromper os Anticoagulantes Orais durante a Intervenção Estomatológica? - António, N (2008)
The management of patients taking long-term oral anticoagulants who require dental surgery is still highly controversial. The risk of bleeding associated with dental treatment under oral anticoagulants must be weighed against the risk of thromboembolism associated with suspension of antithrombotic therapy. Mortality and morbidity associated with thromboembolic events are higher than those associated with hemorrhagic events after minor oral surgery procedures. Evidence-based information does not support oral anticoagulant suspension before minor oral surgery. The authors propose a management protocol for chronically anticoagulated patients who require a dental procedure, to reduce both thromboembolic risk and the risk of bleeding.